PENGEMBANGAN TPACK GURU MELALUI BEDAH MATERI USAHA, ENERGI DAN GELOMBANG DI MGMP FISIKA KABUPATEN JEMBER - Arif, Badrus Sholeh; Supeno; Trapsilo Prihandono (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2024)
The concepts of Work, Energy, and Waves in physics often present challenges for students in Senior High Schools and Madrasah Aliyah due to their complex nature and mathematical applications. To enhance teachers' pedagogical skills in teaching these topics, continuous professional development is necessary. This study aims to improve teachers' mastery of physics content through training that incorporates two approaches: off-site and on-site training. The off-site training, conducted over two months at Madrasah Aliyah Negeri 1 Jember, included material dissection, discussions, and practice in writing teaching materials. Evaluation showed an improvement in teachers' content mastery and success in classroom implementation. The activities focused on designing simple experiments and applying innovative teaching strategies. The findings support the importance of ongoing training and the use of the TPACK framework to enhance the quality of physics teaching. The program is expected to continue with additional training sessions for the professional development of physics teachers in Jember Regency.